Malignant Peripheral Nerve Sheath Tumor and Hypertrophic Osteopathy in a Bitch - Arruda de Souza, Amabile; Guedes Sampaio, Rubia Avlade; Pereira da Silva, Camila; Lima de Oliveira, Rafael; Navarro Marques de Oliveira, Débora Monteiro; Barbosa Lucena, Ricardo (Acta Scientiae Veterinariae, 2020)
Background: Malignant peripheral nerve sheath tumors (MPNSTs) are rare, aggressive, relapsing, metastatic cutaneous neoplasms of mesenchymal origin. So far, no account on the association of this disease with hypertrophic osteopathy (HO) in dogs is available in the literature. Current theories on the possible causes of HO suggest that this disease may be triggered by a primary neoplasm as well as by its metastasis. The objective of this work is to report the clinical, cytological, radiographic, histopathological, and immunohistochemical aspects of a dog affected by MPNST and HO. Case: A 13-year-old female mongrel dog was presented with a history of ulcerated nodular lesion on the skin of the flank. Several ulcerated and non-ulcerated tumors were observed on the thorax, neck, and head at the physical exam. Cytological examination of the nodules revealed presence of mesenchymal cells with a malignant aspect. Complete blood count revealed anemia. There were no alterations in the biochemical tests performed. Thoracic radiographs showed presence of a nodular interstitial pattern in the cranial, medial, and caudal lobes of the lungs. To improve quality of life of the patient, the veterinary team opted for surgical excision of the tumoral ulcerations. Slight claudication in the pelvic limbs was noticed prior to the surgery. Histopathological analyses of the excised nodules verified the existence of malignant mesenchymal neoplasia, which was categorized as peripheral nerve sheath tumor after immunohistochemical examination. Additional cutaneous tumors emerged after surgical excision, along with increased claudication, edema, and pain in the legs. Complete blood count revealed persistent anemia, lymphopenia, monocytosis, and neutrophilia. Radiographs showed an increase in the number and size of the nodules. Radiography of the limbs showed presence of palisading periosteal reaction, and increased radiopacity and volume in the adjacent soft tissues. Doxorubicin and vincristine were administered, but the patient died one week after commencement of the treatment. Discussion: Cytology suggested presence of a malignant neoplasm of mesenchymal origin, and the histopathological and immunohistochemical exams substantiated the diagnosis of malignant peripheral nerve sheath tumor. Macroscopic and histopathological examinations revealed characteristics similar to those described for MPNST in the literature. Positive immunohistochemical reactions for the markers NSE and CD56 determined the diagnosis of MPNST in spite of being negative for S-100, which could represent a consequence of variability in expression and cell differentiation. MPNST exhibits a variable distribution among breeds; it is more predominant in male and elder dogs. Animals exhibiting neoplastic lesions in the thorax, abdomen, head and neck show a high incidence of metastasis after surgical removal of these lesions. The clinical signs of MPNST were unspecific; the alterations observed in the four limbs were observed concomitantly with the diagnosis of hypertrophic osteopathy (HO), and could be due to this condition rather than MPNSC. Histopathological analysis of the pulmonary neoplasms was not possible. However, there is strong suspicion that the pulmonary lesions were a consequence of MPNSC metastasis, which could be the underlying cause of the reemergence of the cutaneous nodules. We believe that HO was caused by the thoracic tumors because the clinical signs became more intense after the increase in the nodules found in the lungs. The difficult diagnosis of MPNSC could be the reason for this type of tumor is rarely identified. MPNSC should always be included in the differential diagnosis for cutaneous tumors, and the possibility that HO represents a consequence of these tumors should be considered.